The Growth anf development of Muslim Cities in Indonesia from the 13th - 18th century - H. Uka Candrasasmita (Puslitbang Lektur dan Khazanah Keagamaan Badan Litbang dan Diklat Kementerian Agama RI, 2012)
tr,1/nr,c.1